Outlawing Genocide Denial : The Dilemmas of Official Historical Truth - Lewy, Guenter, 1923- (Book collections on Project MUSE., 2014)
"Holocaust denial can be viewed as another form of hatred against Jews and restricting it can be understood as a way of preventing hate speech. Germany has made it a crime punishable by law. Other European countries have adopted similar laws. While the rationales for criminalizing speech seems reasonable, Lewy asks readers to look again and to consider carefully the dangers of doing so. His discussion neither dismisses the ramifications of genocide denial nor justifies it; he instead looks closely at the possible risks of government-enforced interpretations of history. By outlawing genocide denial, governments set a precedent for dictating historical 'truth' and how events should be interpreted. Such government restrictions can be counterproductive in a democratic society that values freedom of speech. Lewy examines these and related ideas through the analysis of historical and current examples."--Publisher's Web site.